Maternal Factors Influencing Postpartum Depression in Indonesia - Sari, Nurhalina; Muhani, Nova; Dewi, Friska Novira Maya (UI Scholars Hub, 2023)
The estimated prevalence of postpartum depression differs in developed and developing countries. Due to the increasing number of cases in developing countries like Indonesia, postpartum depression has become a serious issue. This study aimed to identify factors influencing postpartum depression in Bandar Lampung, Indonesia, in 2023 using the Edinburgh Postnatal Depression Scale instrument. This study employed a cross-sectional design with a sample size of 251 respondents, selected based on inclusion and exclusion criteria using a purposive sampling technique. The multiple logistic regression results indicated that women with abortion records had a three times higher risk (95% CI = 1.394–7.648; p-value = 0.013) of experiencing postpartum depression after controlling for other variables (record of depression, employment status, education, and family support). Postpartum women should be followed by midwives and given regular assistance from their loved ones, such as their spouse or family, to prevent depression. These experts can monitor the mother’s well-being and share information on maternal and infant health.